KINETICS OF GIBBSITE DISSOLUTION UNDER LOW IONIC STRENGTH CONDITIONS - V. GIBBSITE SOLUBILITY AT 50°C AND PH 3 TO 9 IN 0.1 MOLAL NACL SOLUTIONS, A GENERAL MODEL FOR AL SPECIATION, AND ANALYTICAL METHODS - Ganor J.; Mogollon J.L.; Lasaga A.C. (My University, 1999)
Experiments measuring synthetic gibbsite dissolution rates were carried out using both a stirred-flow-through reactor and a column reactor at 25°C, and pH range of 2.5-4.1. All experiments were conducted under far from equilibrium conditions (ΔG < -1.1 kcal/mole). The experiments were performed with perchloric acid under relatively low (and variable) ionic strength conditions.An excellent agreement was found between the results of the well-mixed flow-through experiments and those of the (nonmixed) column experiments. This agreement shows that the gibbsite dissolution rate is independent of the stirring rate and therefore supports the conclusion of Bloom and Erich (1987) that gibbsite dissolution reaction is surface controlled and not diffusion controlled.The Brunauer-Emmett-Teller (BET) surface area of the gibbsite increased during the flow-through experiments, while in the column experiments no significant change in surface area was observed. The agreement between the dissolution rates of the mixed flow-through experiments that were normalized to the final surface area, with these of the column experiments, supports the assumption that the changes in surface area occurred early in the experiment, before the first steady state was approached. The significant differences in the BET surface area between the column experiments and the flow-through experiments, and the excellent agreement between the rates obtained by both methods, enable us to justify the substitution of the BET surface area for the reactive surface area.The dissolution rate of gibbsite varied as a function of the perchloric acid concentration. At pH > 3.5 the dissolution rate increased as a function of acid concentration, while at pH < 3.5 it decreased with acid concentration. We interpret the gibbsite dissolution rate as a result of a combined effect of proton catalysis and perchlorate inhibition. Following the theoretical study of Ganor and Lasaga (1998) we propose specific reaction mechanisms for the gibbsite dissolution in the presence of perchloric acid. The mathematical predictions of two of these reaction mechanisms adequately describe the experimental data.